2019
DOI: 10.3311/pptr.13786
|View full text |Cite
|
Sign up to set email alerts
|

Order of the Cities: Usage as a Transportation Economic Parameter

Abstract: On one hand, better and better databases occur through the world, however for cities a lot of important data is unavailable. On the other hand, the cities are one of the most important units, where transportation interactions ought to be analyzed. In this recent paper the order of the cities (based upon the NUTS – Nomenclature des unités territoriales statistiques classification) will be introduced, and an answer will be found for the question whether this parameter could be used as a substitution of an econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Also, it would appear that the tonne-km is the most appropriate indicator to express the road freight transport output at the country level. Economic indicators can be widely used to analyse other transport-related contexts, even at the regional level (Szabó et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, it would appear that the tonne-km is the most appropriate indicator to express the road freight transport output at the country level. Economic indicators can be widely used to analyse other transport-related contexts, even at the regional level (Szabó et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The correlation coefficients are also used in one fuzzy set study to measure the similarity instead of distance functions [25]. In order to find a substitution parameter to represent the transportation economy, the coefficients between several parameters are calculated and presented in scatter diagrams [26]. The authors of [26] found that the introduced parameter "the order of the settlement" represents the correlation between public transportation lines and transportation economy better, within their research limitations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned in the literature review section, having a relatively small sample size is not a critical issue from the MCDM methodology perspective. e consistency ratio of the 15 experts' preferences is checked using equations ( 1) and (2). Table 4 demonstrates the CR values of the experts, which do not exceed 10% in any of the cases.…”
Section: Fahpmentioning
confidence: 99%
“…For several countries, tourism is one of the most important industries in terms of the gross domestic product (GDP) [1]. Data collection about the cities is a relevant issue, where several parameters have to be considered [2]. According to the Hungarian Central Statistical Office, tourism industry is around the fifth of the country's economic activities.…”
Section: Introductionmentioning
confidence: 99%